Bibliometric analysis of global research on physical activity and sedentary behavior in the context of cancer - Gu, Jialin; Hu, Miao; Chen, Yonglin; Yu, Jialin; Ji, Yi; Wei, Guoli; Huo, Jiege (Frontiers in Oncology, 2023)
Objective: Numerous studies focusing on sedentary behavior (SB) and physical activity (PA) in the context of cancer have been reported in recent years. We analyzed and visualized studies on SB and PA in patients with cancer over the last 20 years using scientometric methods, to provide insights on gaps and deficiencies in the literature, and to inform future research guidelines. Methods: All relevant studies in the field from 2001 to October 2022 were reviewed using bibliometric tools, including VOSviewer, Bibliometric online analysis platform, and biblioshiny, to determine the most influential countries, institutions, journals, and authors. We explored current research hotpots and potential research trends, based on keyword clustering and dynamic changes. Our research focuses on PA, SB, and cancer across the entire cancer continuum, from primary prevention to treatment to cancer survivorship. Results: Scientometric analysis identified 4,382 relevant manuscripts on SB and PA in the context of cancer, with a 10-fold increase in articles over the past 20 years. The United States, Canada, and Australia were the most influential countries. The journal, Supportive Care in Cancer, had the highest number of publications, while Clinical Oncology had the highest H-index. K.S. Courneya was the most influential author in this field, with the highest number of publications, total citations, and H-index. Keyword analysis revealed that current research is focused on PA and SB in patients with breast cancer, quality of life, and aerobic exercise. Future frontiers include cancer prehabilitation programs and cardiorespiratory fitness, and remote intervention and social support. Conclusion: By using bibliometrics, we conducted a comprehensive review of SB and PA in cancer-related studies. The current research focused on exercise and sedentariness in breast cancer patients and the role of PA in improving quality of life in survivorship. Emerging research foci were generally around cancer prehabilitation programs and remote intervention issues for PA. In addition, some publication deficits are noted: studies of PA and SB in less common cancers; the recommended doses and intensities of exercise for cancer; the timing of interventions for prehabilitation and the establishment of individualized exercise protocols. These deficiencies align with the needs for future research topics.